Pengembangan Asesmen Formatif Berbasis Socrative untuk Meningkatkan Efektivitas Umpan Balik dalam Mengukur Kerja Ilmiah Siswa: (Development of Socrative-Based Formative Assessment to Improve the Effectiveness of Feedback in Measuring Students' Scientific Work) - Ayinda Puspa, Shynta; Ratna Wulan , Ana (BIODIK, 2026)
Formative assessment plays a crucial role in supporting process-oriented science learning, particularly in measuring and developing students' scientific work. However, assessment practices in schools still tend to focus on outcomes and minimize rapid and meaningful feedback. Therefore, the development of technology-based formative assessment is an urgent need. This study aims to develop a Socrative-based formative assessment and assess the effectiveness of its feedback in measuring students' scientific work. The study used a Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. A limited trial was conducted on high school students, collecting data in the form of a scientific work test based on science process skills and a student perception questionnaire. Data analysis was descriptive. The results showed that most students were in the medium to high scientific work category and had positive perceptions of the use of Socrative-based formative assessment. The real-time feedback was perceived as helping students understand learning outcomes and reflect on them. These findings suggest that Socrative-based formative assessment has the potential to be an alternative assessment that supports more responsive and meaningful biology learning. Abstrak. Asesmen formatif berperan penting dalam mendukung pembelajaran sains yang berorientasi pada proses, khususnya dalam mengukur dan mengembangkan kerja ilmiah siswa. Namun, praktik asesmen di sekolah masih cenderung berfokus pada hasil akhir dan minim umpan balik yang cepat serta bermakna. Oleh karena itu, pengembangan asesmen formatif berbasis teknologi menjadi kebutuhan yang mendesak. Penelitian ini bertujuan mengembangkan asesmen formatif berbasis Socrative serta mengkaji efektivitas umpan baliknya dalam mengukur kerja ilmiah siswa. Penelitian menggunakan pendekatan Research and Development (R&D) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Uji coba terbatas dilakukan pada siswa SMA dengan pengumpulan data berupa tes kerja ilmiah berbasis keterampilan proses sains dan angket persepsi siswa. Analisis data dilakukan secara deskriptif. Hasil menunjukkan bahwa sebagian besar siswa berada pada kategori kerja ilmiah sedang hingga tinggi, serta memiliki persepsi positif terhadap penggunaan asesmen formatif berbasis Socrative. Umpan balik yang diberikan secara real-time dipersepsikan membantu siswa memahami hasil belajar dan melakukan refleksi. Temuan ini menunjukkan bahwa asesmen formatif berbasis Socrative berpotensi menjadi alternatif asesmen yang mendukung pembelajaran biologi secara lebih responsif dan bermakna.